2007
DOI: 10.1111/j.1574-6941.2006.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Arctic and the Antarctic cyanobacteria; three Phormidium-like strains evaluated by a polyphasic approach

Abstract: Selected strains of filamentous Phormidium-like cyanobacteria isolated from two Arctic regions (Ellesmere Island, High Canadian Arctic and Svalbard) and from Antarctica (Antarctic peninsula, South Shetland Islands and South Orkney Islands) were studied. The polyphasic approach used included phenotypic observations of morphological features and genotypic analyses (restriction fragment length polymorphism of 16S rRNA gene, internal transcribed space, 16S rRNA gene sequence analysis). Although genotypes generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
49
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 33 publications
14
49
0
3
Order By: Relevance
“…In our paper a new genus is classified as Wilmottia gen. novum. Comparison with literature sources (Boyer et al 2002;ŠaBacká 2004;caSamatta et al 2005;taton et al 2006;Comte et al 2007;lokmer 2007lokmer , Wood et al 2009heath et al 2010;Strunecký et al 2010b) supported this taxonomic transfer.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In our paper a new genus is classified as Wilmottia gen. novum. Comparison with literature sources (Boyer et al 2002;ŠaBacká 2004;caSamatta et al 2005;taton et al 2006;Comte et al 2007;lokmer 2007lokmer , Wood et al 2009heath et al 2010;Strunecký et al 2010b) supported this taxonomic transfer.…”
Section: Introductionmentioning
confidence: 85%
“…Several phenotypically distinct clusters were also characterized during the study of Antarctic cyanobacterial populations (taton et al 2006, 2010Comte et al 2007;Strunecký et al 2010a), the isolated position of which in phylogenetic trees was confirmed. To such separated clusters belong also group of strains identified traditionally as Phormidium murrayi, described originally from the Antarctica by W. et G.S.WeSt in 1911 as Lyngbya murrayi.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous work on polar cyanobacteria using both morphological and molecular methods in the Polar Regions, has mostly been performed in the Antarctic, where cosmopolitan and endemic taxa are reported (Komárek, 1999;Taton et al, 2003Taton et al, , 2006aJungblut et al, 2005;Comte et al, 2007). By comparison, little is known about Arctic cyanobacteria, which although inhabiting a similar environment, are potentially more connected to temperate latitudes than Antarctica cyanobacteria, which are isolated by the Southern Ocean.…”
Section: Introductionmentioning
confidence: 98%
“…Additional analyses using the ITS region (Comte et al, 2007), multi-locus sequence analyses (Whitaker et al, 2003) and broader genomic and metagenomic analyses are needed to determine whether cold-dwelling oscillatorians belong to narrow ecotypes, analogous to the Synechococcus ecotypes from geothermal springs (Bhaya et al, 2007) and N. commune in Antarctica (Novis and Smissen, 2006). An ecotype may be defined as a group of ecologically similar cyanobacteria, with genetic diversity within the ecotype limited by a cohesive force, either periodic selection or genetic drift, or both (Cohan and Perry, 2007), where in our case the environmental force is extreme cold.…”
Section: Biogeography Of Polar Cyanobacteriamentioning
confidence: 99%